2020
DOI: 10.3390/brainsci10090571
|View full text |Cite
|
Sign up to set email alerts
|

Can We Put Aside Microelectrode Recordings in Deep Brain Stimulation Surgery?

Abstract: Microelectrode recording (MER) in deep brain stimulation (DBS) surgery has long been a recognized and efficient method for defining a target. However, in recent decades, imaging techniques, including DBS surgery, have experienced significant growth. There is convincing evidence that imaging-guided surgery can be helpful for targeting anatomically well-defined nuclei (e.g., subthalamic nucleus (STN) or internal globus pallidus (GPi)), and reductions in secondary effects have also been claimed. It has even been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…In this work, we demonstrated that the neurophysiological properties of the hypothalamus are specific, and PMH can be identified during MER by the type of cells, the presence of atypical EAP and the pattern of discharge, which are different from those noted in the above and below regions. These properties can help to improve the precision of targeting during DBS surgery [ 39 ]. In addition, we described for the first time the presence of atypical EAP that does not fit either the classical depolarization-repolarization description or the three phases observed in the thalamus [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we demonstrated that the neurophysiological properties of the hypothalamus are specific, and PMH can be identified during MER by the type of cells, the presence of atypical EAP and the pattern of discharge, which are different from those noted in the above and below regions. These properties can help to improve the precision of targeting during DBS surgery [ 39 ]. In addition, we described for the first time the presence of atypical EAP that does not fit either the classical depolarization-repolarization description or the three phases observed in the thalamus [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important clinical finding because it could permit the development of a way to specifically identify certain thalamic nuclei without anatomical references and does not need the conscious collaboration of the patient. Therefore, we could perform this type of surgery under general anesthesia, considering the patient’s preferences and well-being, allowing the reduction of stress and discomfort and avoiding awake surgery [ 30 , 31 ]. However, demonstration of this possibility was clearly out of the scope of this work and we merely mention this exciting option.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of MER are clear: MER can safely identify neural structures and borders, MER can help approximate the location within the target that will be most beneficial clinically, and the information gathered from MER can be helpful for understanding disease pathophysiology. MER will likely continue to be an important technique in places that do not yet have access to more advanced imaging techniques ( 39 , 40 ). Although the use of MER does extend the length of the DBS procedure ( 41 ), MER frequently provides important physiologic information that results in lead adjustments up to 20–40% of the time, which can be especially important in instances when there is significant brain shift following preoperative imaging ( 42 , 43 ).…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…The accuracy of these adjustments is dependent on the technique used to adjust the DBS lead ( 40 ). In addition, as imaging and atlas techniques have improved, the role of MER has been called into question ( 39 ). At least one retrospective study has demonstrated no significant differences in mood between asleep and awake DBS cases, ( 44 ) but further work with larger, prospective studies are needed to truly compare the benefits of asleep vs. awake cases.…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%